Multiple gastrointestinal stromal tumors: analysis of clinicopathologic characteristics and prognosis of 20 patients - Li, Kai (Cancer Manag Res, 2019)
PURPOSE: Multiple gastrointestinal stromal tumors (GISTs) are rare. The aim of this study was to investigate the clinicopathologic characteristics and prognosis of multiple GISTs. PATIENTS AND METHODS: Between May 2003 and June 2018, patients who underwent surgery for multiple GISTs were retrospectively analyzed. Exons 9, 11, 13, and 17 of the KIT gene, and exons 12, and 18 of the PDGFRA gene were examined in 34 tumors from 20 patients. RESULTS: A total of 20 patients with multiple GISTs were enrolled. There were 11 females and nine males with a median age of 59 years (range: 37–80 years). Of these cases, 16 were sporadic cases and four were associated with GIST syndromes (two cases of Carney triad and two cases of neurofibromatosis type 1 [NF1]). The most common presentation was gastrointestinal bleeding. Carney triad GISTs did not exhibit KIT/PDGFRA mutations. One of the NF1 patients was a KIT/PDGFRA wild-type, and the other patient had a PDGFRA mutation. Of the sporadic cases, one shared the same KIT gene mutation within each GIST and one had two lesions that were both wild-type for KIT and PDGFRA. Different KIT mutations among individual tumors were detected in seven patients. During the median follow-up period of 66 months (range: 3–183 months), four patients developed liver or abdominal metastases, three of whom expired due to the disease. The rates of recurrence-free survival and overall surviva at 5 years were 65.8% and 76.7%, respectively. CONCLUSION: Multiple GISTs may occur as sporadic tumors or as an additional component of specific syndromes (eg, Carney triad and NF1) that display different clinicopathologic characteristics based on their particular underlying mechanisms. The overall prognosis of patients with multiple GISTs is comparable to that of patients with only a single GIST.